Microbial Powered Down-Flow Hanging Sponge For Nutrient Removal In Sewage Treatment - Tan, Wei Yang (2020)
Significant water pollution has been the great concern to the public due to the discharge of untreated or poor treated wastewater to the environment. Nutrients, particularly phosphorus and nitrogen, are the pollutants that causes the eutrophication and damage of ecosystem due to their enrichment effect. Conventional wastewater treatment plants in Malaysia are ineffective in nutrient removal due to the sewage discharge regulation was only enforced after year 2009 and only applicable to new plant that build thereafter. This research was conducted to design a Down-Flow Hanging Sponge (DHS) system at low cost as a post-treatment of the conventional wastewater treatment plant to remove nutrient. The sewage used in this study was synthetized by using the laboratory chemicals. During the start-up period (Phase 1), the working volume of the DHS reactor was set at 1.5 L per day and was increased to 2 L per day during the commencement of parameter study (Phase 2). Throughout the operation of Phase 1, the DHS reactor showed a simultaneous nitrogen and phosphorus removal. However, negative phosphorus removal was observed due to inadequate operating condition coupled with the enhanced biological pohosphorus removal (EBPR) process carried out by PAOs. Positive phosphorus removal efficiency was then observed during Phase 2 of the study (3.42 – 14.27 %), which was attributed to the proper operating condition that discovered from Phase 1. On the other hand, the removal of nitrogen was much significant than the phophorus removal with nitrification efficiency of 6.91 – 39.43 % in Phase 1 and 2.39 – 21.72 % in Phase 2. The following denitrification efficiency remained high at 20.62 – 98.56 % and 4.39 – 97.42 % at Phase 1 and 2 respectively due to the presence of anaerobic environment at the depth of 0.75 cm from the sponge surface. In addition, the DHS reactor performed well on the removal of COD with removal percentage of more than 90 % at both phases. The sponge matrix with small pores in it acted as a filter to retain the organic matters that flow through it and the high sludge retention time characteristic of the DHS reactor allowed sufficient time for the degradation of organic matters. Therefore, no additional sludge treatment is needed downstream of DHS reactor. Throughout the study, the operating condition or DHS environment had favoured the growth of nitrifiers and denitrifiers, which result in significant vi nitrogen removal. The removal of phosphorus was suppressed due to the presence of anaerobic zone and accumulation of extracellular polymeric substances (EPSs) that restrict the penetration of air into the system. In short, introduction of DHS reactor in conventional sewage treatment for nutrient removal is recommended because the system is able to remove both nutrient and COD. Moreover, it is cost effective and required only small area to build.